The cognitive approach in analyzing legal terms in the international treaties’ texts - Anafinova М.L.; Ormanova А.В. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
Cognitive linguistics dealing with the description and explanation of mental structures and processes connected with language knowledge is viewed as a flexible framework rather than one widely accepted theory; therefore, it is applicable in the study of terms. The article aims to analyze legal terms from cognitive linguistics’ perspective. More specifically, we apply a cognitive approach in interpreting legal terms and explain the way being used in the international treaties’ texts by presenting the document’s frame structure. We reveal the legal document’s frames with the terminals and lexical expressions in Kazakh and English. The study analyzes the agreement document as a script due to a F. Ungerer and H-J. Schmidt’s framework. The terms are undergone the concept structure research technique with presenting paradigmatic and syntagmatic relationships.